79.0k views
5 votes
Can somebody explain how to do this ?

Can somebody explain how to do this ?-example-1

2 Answers

3 votes

Answer:


y=-6 is the correct answer.

Explanation:

The steps involved in solving an algebraic equation in one variable are as stated as:

Step 1: If necessary, simplify the expressions on each side of the equation. This would involve things like removing parentheses, adding like terms, removing fractions.

To remove fractions: Since fractions are another way to write division, and the inverse of divide is to multiply, you remove the fractions by multiplying both sides by the "Least Common Divisor" of all your fractions.

Step 2: Use Addition / Subtraction properties to move the variable term to one side and all other terms to the other side.

Step 3: Use Multiplication / Division properties to remove any values that in front of the variable.

Step 4: Check your answer.

Step-by-Step Solution:


12\left(5+2y\right)=4y-\left(6-9y\right)\\\\\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b+c\right)=ab+ac\\\\\mathrm{Expand\:}12\left(5+2y\right)\:\:=\:\: 60+24y\\\\\mathrm{Expand\:}4y-\left(6-9y\right)\:\:=\:\: 13y-6\\\\60+24y=13y-6\\\\\mathrm{Subtract\:}60\mathrm{\:from\:both\:sides}\\\\60+24y-60=13y-6-60\\\\24y=13y-66\\\\\mathrm{Subtract\:}13y\mathrm{\:from\:both\:sides}\\\\24y-13y=13y-66-13y\\\\11y=-66\\\\\mathrm{Divide\:both\:sides\:by\:}11\\\\(11y)/(11)=(-66)/(11)\\\\y=-6

User Muhammed K K
by
5.9k points
2 votes

Answer:

-6

Explanation:

12(5+2y) = 4y - (6-9y)

60+24y = 4y-6+9y

24y + 60 = 13y - 6

24y-13y = -6-60

11y = -66

y = -6

User Charleslparker
by
5.1k points